Formação acadêmica e produção científica docente em descrição arquivística: um estudo a partir dos cursos de graduação em arquivologia do Brasil - Rego, Laura Maria do [UNESP] (2015)
Although professional training in Archival Science in Brazil dates back to 1911, with the regulatory decree of the National Archive, in 1977 the first university courses on Archival Sciences were implemented in the country, including instructors with diverse backgrounds. However, in the last twenty years, with the expansion of undergraduate courses on Archival Science in Brazil, universities started to require professionals with specific education and experience in the field, something that was taking into account in the allocation of subjects to instructors. In this scenario, the research question is to what extent the subject specificity in the Archival Science instructors' education is related to scientific production. Thus, focusing on the area of archival description, we studied the Lattes curricula of instructors responsible for courses in Archival Science in Brazil, seeking to identify and analyze their education and the scientific production of these instructors, identifying trends and theoretical lines in the area in order to understand to what extent the subject specificity of the instructor's education is related to his/her scientific production. The goal to identify the degree of correspondence between academic education and scientific production based on previous studies of Guimarães (2003) in the field of Library Science. Therefore, we performed a documental exploratory study, through the theoretical review of the trends in archival description, and the analysis of the syllabi of the courses, identifying disciplines that relate to this subject and to the body of instructors. Based on this review, it was possible to reach a set of twenty-three courses, taught by eighteen instructors. Regarding the instructors' education at the undergraduate level, we identified the prevalence (60%) of Archival Science, together with, in lesser incidence, History. At master level, the prevalence (56%) is Information Science, while in...